Astaxanthin attenuates pulmonary fibrosis through lncITPF and mitochondria‐mediated signal pathways. Issue 17 (19th August 2020) - Chen, Hongbin; Wang, Jing; Li, Rongrong; Lv, Changjun; Xu, Pan; Wang, Youlei; Song, Xiaodong; Zhang, Jinjin
Abstract: Pulmonary fibrosis is a chronic interstitial lung disease characterized by pulmonary epithelial injury, fibroblast activation, extracellular matrix deposition, and tissue structure destruction. However, an effective drug treatment remains unavailable. Therefore, studying the mechanism of pulmonary fibrogenesis and finding effective drugs have become important problems in the field of respiratory diseases. Pulmonary fibrosis is typically characterized by activated fibroblast proliferation and migration. Hence, abnormality in activated fibroblast proliferation and migration is a major concern for treating pulmonary fibrosis. Long noncoding RNA (lncRNA) is an enigmatic subclass of ncRNA that regulates various fundamental biological processes and participates in disease occurrence and development. However, studies on lncRNA as the therapeutic target of drug action are rarely reported. Our group first identified differentially expressed lncRNAs and revealed that lncITPF is a highly upregulated lncRNA in lung fibrosis. In particular, lncITPF is detected in the blood of patients with idiopathic pulmonary fibrosis. Clinical analysis shows that lncITPF is positively correlated with the degree of fibrosis. The receiver operating characteristic (ROC) curve indicates that the specificity and sensitivity values are 95.0 and 64.3, respectively. The area under the ROC curve is 0.804, indicating that lncITPF can be a diagnostic biomarker for IPF. However, whether lncITPF is effective as a therapeutic target of drug action against pulmonary fibrosis remains unclear. In this study, lncITPF acting as the therapeutic target of astaxanthin was explored in depth. The findings elucidated that astaxanthin blocks the activated fibroblast proliferation and migration through lncITPF and mitochondria‐mediated signal pathways to alleviate pulmonary fibrogenesis.